Changes in mortality among patients with chronic obstructive pulmonary disease from the 1990s to the 2000s: a pooled analysis of two prospective cohort studies - Koichi Nishimura; Toru Oga; Naoya Tanabe; Susumu Sato; Shigeo Muro; Toyohiro Hirai; Kazuya Tanimura (BMJ Open, 2023)
Objectives This study aimed to identify and investigate changes in the mortality of patients with chronic obstructive pulmonary disease (COPD) at the same institute from the 1990s to the 2000s. We hypothesised that the improvement in long-term mortality of COPD was achieved due to the development of pharmacological and non-pharmacological treatments.Design This study was a retrospective analysis of two observational prospective cohort studies. One study enrolled subjects from 1995 to 1997 (the 1990s), and the other enrolled subjects from 2005 to 2009 (the 2000s).Setting Two studies from a single centre, which was the same university hospital in Japan.Participants Patients with stable COPD.Primary and secondary outcome measures We analysed all-cause mortality data from the pooled database. Subanalyses were conducted by stratifying subjects into two groups according to airflow limitation severity as severe/very severe (per cent predicted value of forced expiratory volume in 1 s (%FEV1) <50%) or mild/moderate (%FEV1≥50%).Results In total, 280 male patients with COPD were enrolled. Patients in the 2000s (n=130) were significantly older (71.6 vs 68.7 years) and had milder disease (%FEV1; 57.6% vs 47.1%) than those in the 1990s (n=150). Almost all severe/very severe patients in the 2000s received long-acting bronchodilators (LABDs), and they had a significantly lower risk of mortality than those in the 1990s according to Cox proportional regression analyses (OR=0.34, 95% CI 0.13–0.78), with a 48% reduction in 5-year mortality (from 31.0% to 16.1%). Moreover, any LABD use had a significantly positive impact on prognosis, even after adjustments for age, FEV1, smoking status, dyspnoea, body size, oxygen therapy and study period.Conclusions Trends indicating a better prognosis for patients with COPD in the 2000s were observed. This improvement may be associated with the usage of LABDs.